Green norms in the workplace to promote environmental sustainability: the positive effect on green innovative work behaviors and person-environment relationship - Dibattista, Ilaria; Berdicchia, Domenico; Mazzardo, Elena; Masino, Giovanni (Frontiers in Sustainability, 2025)
IntroductionThis study explores the relevance of behavioral and psychological factors in contributing to organizational environmental sustainability in the workplace.MethodsData were obtained from 271 workers in 5 organizations operating in the manufacturing sector in Italy and analyzed through a regression methodology. We tested two models, in which the employees’ perception of the work climate is derived from different sets of norms. In one model, we explored the influence of organizational policies and practices (injunctive norms). In another model, we explored the influence of peers’ behavior (social, descriptive norms).ResultsThe results show a positive impact of the employees’ perception of their work climate on both their propensity to engage in innovative green behaviors and their sense of personal connection with the environment, via environmental commitment. Moreover, we found that the employee’s organizational identification positively moderates the effect on green innovative behavior.DiscussionThis study underscores the relevance of creating and maintaining a pro-environment work climate in order to foster pro-environment innovative behavioral changes. Also, the results indirectly suggest that the influence on the sense of personal connection with the environment may generate a positive spill-over effect into the private life of workers.